Gadolinium Deposition in the Brain: A Systematic Review of Existing Guidelines and Policy Statement Issued by the Canadian Association of Radiologists. Issue 4 (November 2018) - Costa, Andreu F.; van der Pol, Christian B.; Maralani, Pejman Jabehdar; McInnes, Matthew D.F.; Shewchuk, Jason R.; Verma, Raman; Hurrell, Casey; Schieda, Nicola
Emerging evidence has confirmed that, following administration of a gadolinium-based contrast agent (GBCA), very small amounts of gadolinium will deposit in the brain of humans with intact blood-brain barriers. The literature is evolving rapidly and the degree to which gadolinium will deposit for a particular GBCA or class of GBCAs remains undetermined. Several studies suggest that linear GBCAs deposit more gadolinium in the brain compared with macrocyclic GBCAs; however, our understanding of the molecular composition of deposited gadolinium is preliminary, and the clinical significance of gadolinium deposition remains unknown. To date, there is no conclusive evidence linking gadolinium deposition in the brain with any adverse patient outcome. A panel of radiologists representing the Canadian Association of Radiologists was assembled to assist the Canadian medical imaging community in making informed decisions regarding the issue of gadolinium deposition in the brain. The objectives of the working group were: 1) to review the evidence from animal and human studies; 2) to systematically review existing guidelines and position statements issued by other organizations and health agencies; and 3) to formulate an evidence-based position statement on behalf of the Canadian Association of Radiologists. Based on our appraisal of the evidence and systematic review of 9 guidelines issued by other organizations, the working group established the following consensus statement. GBCA administration should be considered carefully with respect to potential risks and benefits, and only used when required. Standard dosing should be used and repeat administrations should be avoided unless necessary. Gadolinium deposition is one of several issues to consider when prescribing a particular GBCA. Currently there is insufficient evidence to recommend one class of GBCA over another. The panel considered it inappropriate to withhold a linear GBCA if a macrocyclic agent is unavailable, if hepatobiliary phase imaging is required, or if there is a history of severe allergic reaction to a macrocyclic GBCA. Further study in this area is required, and the evidence should be monitored regularly with policy statements updated accordingly.